A Ray of Hope against Parthenium in Rajaji National Park? - Goyal, C. P.; Brahma, B. C. (Indian Forester, 2001)
Rajaji National Park (Uttaranchal), the home of Elephants, Tigers and various other flora and fauna has been invaded by the noxious weed Parthenium hysterophorus in many of its open areas affecting the availability of food for herbivores. In June 1999, a leaf-eating beetle was observed feeding on Parthenium hysterophorus in an area of 3 hectare in Chirak Block of Haridwar Range. The beetle has been identified as the Mexican beetle, Zygogramma bicolorata of Chrysomelidae family. A survey was done, in which it was observed that, while in July 1999, the affected area comprised of 3 ha only, during July 2000, the area had increased to 37 ha in the same Range. It was also observed that the beetle had attacked an additional area of 1.5 ha of Parthenium hysterophorus in Motichur Range. On an average, mortality per cent of Parthenium hysterophorus appears to depend on the number of beetles affecting the area. Further research needs to be carried out to determine the potential impact, if any, on non-target species, the life cycle of the beetle, its adaptation to different climates, its predators, the rate of spread of affected Parthenium hysterophorus areas and the feasibility of attack by the beetle before the onset of flowering of Parthenium hysterophorus plants.